Outcome of Tobacco Smoking Habit on Lipid Peroxidation and Antioxidant parameters in Anemic Individuals - Madhikarmi, Nirjala Laxmi; Gautam, Madhav (Birat Journal of Health Sciences, 2021)
Introduction: Globally tobacco smoking is considered as a foremost public health problem. Erythrocytes membrane lipids are rich in polyunsaturated fatty acids and the oxidative effects of oxygen on its membrane are greater than other tissues and the condition is heightened by tobacco smoke.Free radicals present in the tobacco increases peroxidation products in blood and vascular tissues are chiefly responsible for harmful effects. Objective: The present study was designed to investigate the impact of stress induced by tobacco smoke on lipid peroxidation and antioxidant parameters in patients with anemia. Methodology: A hospital-based case-control study was carried out in Kantipur Dental College Teaching Hospital, included 150 tobacco smoking anemic and 150 healthy volunteers. The stress parameter was assessed by the determination of malondialdehyde, lipid hydroperoxide and nitric oxide. The non-enzymatic antioxidants such as vitamins A, C and E and total antioxidant activity and enzymatic antioxidants were catalase, superoxide dismutase and glutathione peroxidase were also determined. Result: Hemoglobin level in anemic smokers showed raised level as compared to healthyindividualsbut there was diminished antioxidants status and elevated free radical parameters in anemic smokersdespite their raised hemoglobin status.We found statistically increased malondialdehyde, lipid hydroperoxide and nitric oxide levels and decreased enzymatic and non-enzymatic antioxidant status, thus increasing the oxidative stress. Conclusion: The present study showed high concentration of hemoglobin, low status of non-enzymatic antioxidants and high levels of oxidants as compared to controls reflecting the destructive and oxidative effects of tobacco smoke.